When bad behaviour pays: North Korea and the global nuclear order - Howell, E (2021)
This thesis analyses the state behaviour of the Democratic People’s Republic of Korea (North Korea/DPRK) with respect to international order, focusing upon the global nuclear order. In so doing, this thesis argues that North Korea, under certain circumstances, engages in behaviour that breaks the rules of international order and the nuclear order owing to the benefits that may be gained. Although existing literature in International Relations argues how norm-breaking behaviour within international society is met with opprobrium and the infliction of negative status, such scholarship overlooks the idea that deviant behaviour can, in fact, catalyse positive outcomes. In making this argument, this thesis pioneers the novel framework of strategic delinquency, which, at its core, focuses on three types of delinquent behaviour – provocations; norm-transgression; deception – that can be exercised in pursuit of particular material and social benefits: material benefits comprise deterrence, regime survival, and economic assistance; social benefits relate to three types of recognition, namely recognition as a sovereign, equal, and exceptional actor.